Urban flooding, social equity, and "backyard" green infrastructure: An area for multidisciplinary practice. Issue 3 (2nd October 2019) - Mason, Lisa Reyes; Ellis, Kelsey N.; Hathaway, Jon M.
ABSTRACT: "Backyard" green infrastructure programs are an innovative way to manage urban stormwater, with many social and ecologic benefits. In many programs, however, residents with lower incomes are not reached, though they could benefit from participation, and though their participation could benefit the socioecological system. We examined awareness of and interest in backyard green infrastructure among lower- and moderate-income residents (N = 234). Awareness among our study population is low to moderate, but interest is moderate to high, with variability by some demographic and other characteristics. A spouse/partner, city agency, and/or neighbor may have influential roles in increasing participation in backyard green infrastructure.